Implementation of Strategic Management in Improving Educational Quality; an Analysis of a Thailand Islamic Educational Institution - Muhammad Ali Radja Fath; Isra Hayati (STAI Serdang Lubuk Pakam, 2023)
The purpose of this study was to analyze the implementation of strategic management in the management of educational institutions at SD Darul Muhmin School Thailand. This research method uses a qualitative approach with descriptive research methods. The method of collecting information uses interviews, documentation and observation. The respondents in this study were the Principal and Management of the Darul Muhmin School Thailand Foundation. The results showed that the implementation of strategic management in the management of educational institutions at SD Darul Muhmin School Thailand was carried out well, this can be seen from the increasing number of students at SD Darul Muhmin School every year, then the creation of quality, superior, and morally good students in accordance with the vision and mission of SD Darul Muhmin School Thailand. Strategic management implemented at SD Darul Muhmin School Thailand is in the form of learner management, curriculum management, personal management, infrastructure management, and budget management. This research provides recommendations for improving the management of educational institutions, especially Islamic-based.